Peran Gereja dan Hamba Tuhan dalam Menghadapi Perilaku Intoleransi dan Fundamentalis - Jhon Leonardo Presley Purba (APOSTOLOS, 2021)
Indonesia is the most plural country in the world. Pluralism in Indonesia also concerns religion. The role of the Church and the Servant of God is very important in dealing with intolerant behavior between religions in the pluralism of the Unitary State of the Republic of Indonesia. This research is a descriptive qualitative research that uses literature research methods and data collection using the literature study method. The purpose of this research is to find out how the role of the Church and the Servant of God in dealing with intolerant behavior and religious hardliners within the framework of the Republic of Indonesia. Using descriptive qualitative methods with a phenomenological approach through literature studies designed to collect, analyze and compile systematic and scientific valid data from literature materials relevant to this research, so that the conclusion of this study is that the Church and the Servant of God have an important role. to be proactive in maintaining and dealing with intolerant behavior towards Christians in Indonesia by being responsible for educating Christians in Indonesia so that they do not have radical sectarianism that leads to aggressive and intolerant behavior towards adherents of other religions. The Church and the Servant of God must realize that every citizen has the right that is protected by the state to worship according to the religion and belief of each citizen. If there is an intervention against Christians exercising their religious rights, the Church and the Servant of God must act to defend their rights as citizens according to the laws in force in Indonesia by making various efforts including through inter-religious dialogue approaches, social approaches, political approaches and formal legal approaches according to the law applies in Indonesia.